Konsep Sistem Informasi Manajemen Dakwah - Erwan Efendi; Indah Anugrah; Bagus Triady; M. Ariiq Hawarri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to find out how to understand the da'wah management information system. The da'wah management information system is an information system for da'wah management which is structured using formal procedures, with the aim of providing relevant information to managers, both internal information and external information in all the relevant organizational functions, so that decision making can be carried out effectively. . The role of this da'wah management information system is as a tool used to describe in fact the circumstances and situations both internal. So with the existence of an increasingly sophisticated da'wah management information system, it is able to bring and make it easier for preaching to be more effective. As we can see with the emergence of information systems in the form of computers, cellphones that have a wider range can make it easier for us to access da'wah without coming to the place. Keywords: System, Information, Management and Da'wah